Background
The stimulus-responsive hydrogel is used as a functional hydrogel, and has the characteristics of water absorption, swelling and non-dissolution of the traditional hydrogel and the swelling and non-swelling behaviors under the external stimulus response. A stimulus-responsive shape-deformable hydrogel is a smart hydrogel that can undergo controlled, reversible shape changes under a variety of chemical and physical stimuli (e.g., light, electricity, temperature, magnetic fields, ions, humidity, etc.). Stimulus-responsive hydrogels have become "star" materials for the development of intelligent drive systems due to their softness, high aqueous properties, and ease of functionalization. The hydrogel can form reliable interaction with a biological interface by combining inherent biocompatibility, self-adaptability, mechanical strength of similar tissues and other characteristics of the hydrogel, and further has good application prospects in various medical scenes such as soft medical robots, tissue regeneration, cell manipulation, artificial muscles, drug delivery and the like.
In view of the unique advantages of stimulus responsive hydrogel actuators, researchers have focused on developing a variety of advanced techniques to achieve "on-demand" conversion of a two-dimensional plane to a three-dimensional configuration. The common strategy is to control the anisotropy (such as crosslink density, composition, filler distribution/direction, etc.) inside the hydrogel by photolithography, molding, 3D/4D printing, electrodeposition, etc. to allow it to respond to external stimuli such as light, temperature, magnetic field, and electric field. In addition, encapsulation of the active component with functionality into a homogeneous hydrogel matrix is also an effective method of preparing a deformation actuator.
In document "Reconstructable Gradient Structures and Reprogrammable 3DDeformations of Hydrogels with Coumarin Units as the Photolabile Crosslinks" hydrogels are prepared by polymerizing hydrophilic acrylic micelles using hydrophobic coumarin monomers. The presence of cetyl trimethylammonium chloride micelles increases the local concentration of coumarin units and improves the mechanical properties of hydrogels by forming strong polyelectrolyte/surfactant complexes as physical crosslinks. The high-efficiency photodimerization and photocleavage reaction of coumarin are respectively realized under 365nm and 254nm light irradiation, and the reversible regulation and control of the hydrogel network structure are realized. The ordered arrangement of different gradient structures in one hydrogel is realized through a photoetching technology, and the deformation of the hydrogel is guided into different structures. This strategy should be applicable to other photosensitive hydrogels to achieve reversible programming control and multi-function of the network structure.
The invention patent with publication number CN106977649A discloses a preparation method of a hydrogel actuator with controllable deformation. The deformation-controllable hydrogel actuator is formed by mixing an isopropyl acrylamide monomer, an initiator and an inorganic nanomaterial to form a uniform pre-gel. The inorganic nano material comprises one or more of magnesium lithium silicate clay, montmorillonite, layered double hydroxide, graphene oxide, calcium carbonate nano particles and ferroferric oxide nano particles. Pouring the pregel into a rectangular mold, covering a layer of mask plate on the surface of the pregel, evaporating part of water to induce the concentration of the inorganic nano material to be unevenly distributed in the thickness direction of an exposed area, and then in-situ polymerizing to fix the patterned uneven structure, thereby forming the hydrogel actuator with controllable deformation.
By utilizing the developed strategies, great progress has been made in controllable, reversible programming, multi-mode deformation functions and the like, and the application of the shape-deformed hydrogel in different fields is greatly promoted. However, most of the hydrogel systems are constructed from synthetic polymers, and generally involve complex molecular tissues and cumbersome synthetic procedures. In addition, as the application of the shape-deformable hydrogel in biomedical fields has been developed, new requirements are put on the required materials, which are expected to have better reproducibility and biocompatibility.
Thus, there is an urgent need to develop an actuator compatible with physiological environments, which has both environmental friendliness and biocompatibility, a simple structural design, multi-modal and reprogrammable shape changes, and functional integration, through a simple and green manufacturing process.
Disclosure of Invention
The invention aims at overcoming the defects of the prior art and provides a preparation method of deformable silk fibroin gradient hydrogel. The invention prepares uniform hydrogel through free radical crosslinking of silk fibroin tyrosine residues catalyzed by horseradish peroxidase in the presence of hydrogen peroxide, then induces silk fibroin molecular chains to migrate under the action of an electric field, and further forms gradient hydrogel with anisotropically distributed protein network, after the electric field is removed, the hydrogel deforms due to the existence of internal stress, and the deformable gradient hydrogel can be stably combined with a biological tissue interface, so that the deformable gradient hydrogel can be used as various biological integrated devices.
In order to achieve the above purpose, the present invention adopts the following technical scheme:
a method for preparing deformable silk fibroin gradient hydrogel, comprising the following steps:
s1: degumming silkworm cocoons to prepare degummed silk, dissolving the degummed silk and dialyzing to obtain silk fibroin solution;
s2: adding an oxidation-reduction agent and a catalyst into the silk fibroin solution of the S1, and uniformly mixing to obtain a crosslinking reaction mixed solution;
s3: injecting the crosslinking reaction mixed solution of the S2 between two transparent electrodes under the assistance of a mold, and obtaining the silk fibroin uniform hydrogel after the crosslinking reaction;
s4: and (3) applying a direct current electric field between the two transparent electrodes in the step (S3), and obtaining the variable silk fibroin gradient hydrogel through the action of the direct current electric field.
Further, in step S1, the degumming treatment method includes: dissolving anhydrous sodium carbonate in boiling water to prepare sodium carbonate solution with the concentration of 0.02M, adding silkworm cocoon fragments into the solution, boiling for 30min to remove sericin, rubbing with deionized water for 3-5 times, and drying to obtain degummed silk.
Further, in step S2, the redox agent is hydrogen peroxide.
Further, in step S2, the catalyst is horseradish peroxidase.
Further, in step S2, the redox agent and the catalyst are used in an amount of 0.2 to 2.6mg of the redox agent and 0.7 to 0.9mg of the catalyst per 1g of the silk fibroin, based on the mass of the silk fibroin in the silk fibroin solution.
In step S3, the crosslinking reaction time is 10-15h, and the temperature is room temperature.
In step S3, the mold material includes, but is not limited to, a polymer material such as polymethyl methacrylate (PMMA), polydimethylsiloxane (PDMS), and the like, and the transparent electrode includes, but is not limited to, a conductive material such as Indium Tin Oxide (ITO) glass plate.
In step S4, the direct current electric field strength is 1-10V/mm, and the electric field acting time is 1-600S. The silk fibroin gradient hydrogel is obtained through the integral migration of a silk fibroin network, and the bending deformation degree of the hydrogel can be adjusted by regulating the action time of an electric field.
Further, step S4 employs the following method instead: by CO 2 And (3) carrying out laser cutting on the silk fibroin uniform hydrogel in the step (S3) by a laser cutting machine to obtain the silk fibroin uniform hydrogel with a set shape, and then applying a direct current electric field to the silk fibroin uniform hydrogel for treatment to obtain the silk fibroin gradient hydrogel. By changing the parameters of the electric field, the shape of the cut hydrogel and the area of the applied external electrode, deformable hydrogels of different geometries can be obtained, enabling the construction of different three-dimensional shapes.
The deformable silk fibroin gradient hydrogel prepared by the method is applied to a biological integrated device. The bio-integrated device includes a bio-tissue functional interface and a bio-electrode.
When the deformable silk fibroin gradient hydrogel is used as a biological tissue functional interface, the deformable silk fibroin gradient hydrogel has good adhesion and binding capacities in air and water; the silk fibroin gradient hydrogel and the carbon nano tube can be compounded in a multilayer manner to construct a bioelectrode which is used for electric stimulation conduction.
The invention has the beneficial effects that:
1. the invention provides a preparation method of deformable silk fibroin gradient hydrogel, which utilizes simple horseradish peroxidase catalysis to realize rapid crosslinking of silk fibroin networks, and can drive gradient distribution of the silk fibroin networks under a low-voltage electric field.
2. The invention can change the bending deformation degree of the hydrogel by adjusting the action time of the electric field, and can obtain the deformed hydrogel with different three-dimensional configurations by arranging the direction and the area of the electric field and combining the laser cutting process, so that the deformed hydrogel has better attaching and combining capability with different biological tissues in air and water environment, and a good hydrogel-tissue interface is formed.
3. The random coil conformation of silk fibroin in the hydrogel is not changed under the action of an electric field, so that the deformation gradient hydrogel can restore the original uniform network morphology through the soaking action of water, the reprogramming of the three-dimensional configuration of the hydrogel is realized, and the utilization efficiency and the rewriting capability of the hydrogel are greatly improved.
4. According to the invention, the three-dimensional configuration of the hydrogel can be permanently fixed by inducing the silk fibroin to generate conformational transition through ethanol, so that the hydrogel can maintain a stable form in water environment.
5. The invention prepares a fully flexible bioelectronic device by compounding the silk fibroin gradient hydrogel and the carbon nano tube, and uses the fully flexible bioelectronic device as a bioelectrode to coat the sciatic nerve of an animal, thereby realizing good electric stimulation conduction.
Detailed Description
The following is a further detailed description of embodiments of the present invention in conjunction with specific examples, which are not intended to limit the scope of the invention, so that those skilled in the art may better understand the technical means of the present invention and practice it. It should be further noted that, for convenience of description, only some, but not all of the matters related to the present invention are shown in the accompanying drawings.
Example 1
A method for preparing deformable silk fibroin gradient hydrogel, comprising the following steps:
s1: dissolving 21.2g of anhydrous sodium carbonate in 10L of boiling water to obtain a sodium carbonate solution with the concentration of 0.02M, adding 25g of silkworm cocoon fragments into the solution, boiling for 30min (stirring every 5 min), taking out, rubbing with deionized water for 4 times, wringing, transferring into a fume hood, and drying to obtain degummed silk; adding degummed silk into 9.3M lithium bromide solution according to the mass ratio of 1:4, dissolving for 4 hours at 60 ℃, transferring the obtained solution into 3500kDa dialysis bag for dialysis for 3 days, centrifuging for 20 minutes at 11000rpm, filtering the supernatant to obtain silk fibroin solution, and measuring the mass fraction of the silk fibroin solution to be 6wt% by adopting a drying weighing method; after marking, the obtained product is stored in a refrigerator at the temperature of 4 ℃ for 10 to 14 days.
S2: 0.4g 250U/mg horseradish peroxidase (HRP) powder is added into 10mL deionized water and mixed uniformly to obtain 40mg/mL HRP stock solution with the concentration of 10,000U/mL. 100. Mu.L of 30wt% hydrogen peroxide (H) 2 O 2 ) 29.9mL of deionized water was added to give a H concentration of 0.1wt% 2 O 2 Standby;
43.2mL of the silk fibroin solution prepared by S1 is taken in a 50mL centrifuge tube, and then added51.6 mu LHRP stock solution and 6.8mL of 0.1wt% H 2 O 2 And (3) uniformly mixing the solutions to obtain a crosslinking reaction mixed solution.
S3: transferring the crosslinking reaction mixed solution of S2 into a Polydimethylsiloxane (PDMS) mould with the thickness of 10cm multiplied by 10cm, and clamping the mixture between two pieces of Indium Tin Oxide (ITO) glass with the resistance of 6 omega serving as a cathode and an anode, and reacting for 12 hours at room temperature to obtain silk fibroin uniform hydrogel;
s4: and connecting an external electric field and an ITO plate through a wire, applying a direct current electric field with the voltage of 1V/mm, inducing the whole negatively charged protein network structure to migrate to the anode side, and respectively setting the action time of the electric field to be 20s, 40s, 60s, 120s, 300s and 600s to obtain the silk fibroin gradient hydrogel (respectively named as gradient hydrogel-20, gradient hydrogel-40, gradient hydrogel-60, gradient hydrogel-120, gradient hydrogel-300 and gradient hydrogel-600) after the completion.
FIG. 1 is a cross-sectional scanning electron microscopy image of a silk fibroin gradient hydrogel (gradient hydrogel-60) prepared in example 1, wherein FIG. 1i is a cross-sectional scanning electron microscopy image of gradient hydrogel-60 near the cathode, FIG. 1iii is a cross-sectional scanning electron microscopy image of gradient hydrogel-60 near the anode, and FIG. 1ii is a cross-sectional scanning electron microscopy image of the middle portion of gradient hydrogel-60. It can be seen that the gradient hydrogel-60 decreases in size from the cathode side to the anode side, indicating that a gradient network is formed in the hydrogel under electric field stimulation, and migration of the protein network to the anode results in higher crosslink density and smaller pore size in the vicinity thereof.
The curvature of the gradient hydrogel was measured at different electric field application times and compared to the electric field application time of 0, the test results are shown in fig. 2. Fig. 2 shows the curvature measurement results of the gradient hydrogel under different electric field application times, and it can be seen that the hydrogel is straight-bar-shaped when the electric field application time is 0, and is changed into arc-shaped when the electric field application time is 1V/mm, and the curvature increases with the increase of the application time.
Example 2 preparation of silk fibroin gradient hydrogels in combination with laser cutting Process
Steps S1-S3 are the same as in example 1, S4 being modified as follows:
s4: by CO 2 A laser cutting machine (speed 100R, trotec laser, austria), wherein a lens is firstly wiped clean by a lens wiping liquid and a lens wiping paper, the machine is positioned and initialized, and computer operation software is connected with the cutting machine; leading a pre-designed hydrogel pattern (in the embodiment, a cross shape) into computer operation software, fixing the silk fibroin uniform hydrogel of S3 on an aluminum plate, putting the aluminum plate on a laser cutter working platform, adjusting the height, setting a cutting initial point, and setting laser power intensity and speed, wherein working parameters are as follows: laser power 25%, cutting speed 1step/s; after cutting, obtaining cross-shaped silk fibroin uniform hydrogel, clamping the uniform hydrogel between two ITO conductive plates, respectively connecting an upper polar plate and a lower polar plate with a positive electrode and a negative electrode of a power supply, and applying a direct current electric field of 1V/mm to treat for 300s to obtain silk fibroin gradient hydrogel.
Example 3
The pre-designed hydrogel pattern was windmill-shaped, sandwiching the windmill area between two ITO conductive plates, the remainder being the same as in example 2.
Example 4
The pre-designed hydrogel pattern was in the form of a strip, a pair of electrodes were applied to each end of the strip, the electrodes were placed in opposite directions, and the rest was the same as in example 2.
Fig. 3 is a photograph of silk fibroin gradient hydrogel obtained in examples 2 to 4, wherein fig. 3A1 and 3A2 correspond to hydrogel after laser cutting and gradient hydrogel after direct current field treatment in example 2, fig. 3B1 and 3B2 correspond to hydrogel after laser cutting and gradient hydrogel after direct current field treatment in example 3, respectively, and fig. 3C1 and 3C2 correspond to hydrogel after laser cutting and gradient hydrogel after direct current field treatment in example 4, respectively, and it can be seen that bud-shaped gradient hydrogel is obtained in example 2, gradient hydrogel after twisting and bending four arms of windmill is obtained in example 3, and 8-shaped gradient hydrogel is obtained in example 3. This demonstrates that the silk fibroin gradient hydrogels of the present invention can achieve controllable and programmable shape changes.
Performance testing
1. In vitro cytotoxicity and in vivo biocompatibility testing of deformable silk fibroin gradient hydrogels
(1) In vitro cytotoxicity test: cytotoxicity of the gradient hydrogels was assessed using a cell counting kit (CCK-8) and stained with a live/dead kit. Briefly, bone marrow mesenchymal stem cells (BMSCs) were seeded into 96-well plates at a density of 5000 cells/well and in an incubator (37 ℃,5% CO) 2 ) Is cultured. The sample of the gradient hydrogel prepared in example 1 (gradient hydrogel-60) was exposed to ultraviolet light for 1h for sterilization. After placing the samples in 24-well plates, BMSCs were seeded and maintained on gradient hydrogels at a density of 5000 cells/well and in an incubator (37 ℃,5% CO) 2 ) Co-cultivation was performed in medium culture for 24 hours. After co-cultivation, 10. Mu.L of CCK-8 was added to each well, followed by cultivation at 37℃for 2 hours. Cell culture media without sample was used as control group. Cell viability was determined using a multifunctional microplate reader (EnSpire, perkinElmer, US) at a wavelength of 450 nm. Assays were performed in 5 duplicate wells and 3 replicates were performed per sample. In the live/dead test, BMSCs were seeded on silk fibroin gradient gels at a density of 250000 cells per well and incubated in an incubator (37 ℃,5% CO 2 ) Is cultured for 24 hours. BMSCs were stained with a live/dead kit in the dark for 15min and photographed under an Olympus TH4-200 fluorescence microscope (Olympus Corporation, japan). And cytotoxicity was quantitatively analyzed by calculating an optical density (OD, representing cell density) value.
The in vitro cytotoxicity test results of the deformable silk fibroin gradient hydrogel prepared in example 1 are shown in fig. 4, and it can be seen that the OD value at 450nm of the cells co-cultured with the silk fibroin gradient hydrogel after 24 hours of culture was similar to that of the control (original cell culture medium), indicating that the experimental sample had lower cytotoxicity.
(2) In vivo biocompatibility test: the gradient hydrogels were prepared in a sterile manner and sterilized by ETO and UV treatment. 8 week old Kunming mice were anesthetized with isoflurane (1-3% oxygen) in an anesthetic chamber. The back hair of the mice was cut, the subcutaneous tissue was cut and exposed, and then a hydrogel sample (gradient hydrogel-60 prepared in example 1) was implanted subcutaneously. The mice were sacrificed by carbon dioxide inhalation 14 days after implantation. Subcutaneous tissue was excised, fixed with 10% formalin, the harvested tissue was stained with hematoxylin and eosin (H & E) and histologically analyzed, and protein (. Alpha. -SMA, CD68, COL-I) expression was assayed by immunofluorescent staining.
In order to characterize the immune response elicited by silk fibroin gradient hydrogels in vivo, immunofluorescent staining studies were performed on biomarkers associated with inflammation induced by foreign body response and tissue regeneration, including CD68 of macrophages, α -smooth muscle actin (α -SMA) of fibroblasts, and collagen type I collagen (COL-I), respectively.
FIG. 5 shows the results of in vivo biocompatibility tests of the deformable silk fibroin gradient hydrogel prepared in example 1, wherein FIG. 5A shows the expression level of CD68, FIG. 5B shows the expression level of α -SMA, and FIG. 5C shows the expression level of COL-I, and it can be seen that no significant biomarker expression was observed in subcutaneous tissue implanted in the hydrogel, indicating that the hydrogel has good in vivo biocompatibility.
2. Conformal binding test of deformable silk fibroin gradient hydrogels and biological tissues
The experimental method comprises the following steps:
after silk fibroin uniform hydrogel (SF-H-gel) was prepared by the method of example 1, CO was used as in example 2 2 The method comprises the steps of cutting into a circular shape, a cross shape and a strip shape by a laser cutting machine, applying an external electric field effect to obtain three deformable silk fibroin gradient hydrogels (SF-G-gel) with specific curvature and three SF-H-gels with the circular shape, the cross shape and the strip shape serving as a reference, respectively attaching the three SF-G-gels to the surfaces of resin eyeballs, rabbit hearts and rabbit thighbones, observing attachment conditions, transferring the attachment conditions into water, and observing attachment conditions again.
Fig. 6 is a photograph of a deformable silk fibroin gradient hydrogel combined with various biological tissues, and it can be seen that three deformable silk fibroin gradient hydrogels with a certain curvature can be tightly attached along the curved resin eyeball and the irregularly shaped rabbit heart and rabbit femur surfaces without additional fixation, and the hydrogel on the surface is still fixed on the resin eyeball, rabbit heart and rabbit femur surfaces after being transferred into water. In contrast, silk fibroin homogeneous hydrogels SF-H-gel do not form good hydrogel-tissue interfaces with organs, especially in aqueous environments.
3. Application testing
The preparation method of the carbon nano tube/silk fibroin gradient hydrogel double-layer strip comprises the following steps:
step 1, preparing a carbon nano tube: an aligned array of Carbon Nanotubes (CNT) is first synthesized by chemical vapor deposition. Depositing Fe (1.5 nm) and Al on a silicon substrate using an electron beam evaporator (DZS-500, shenyang Keyi, china) 2 O 3 (5 nm) as catalyst. C at a flow rate of 90sccm 2 H 2 As carbon source, ar and H 2 Is a carrier gas. Growing at 740 ℃ for 10min. 15 carbon nanotube sheets were removed from the carbon nanotube array and transferred to a polytetrafluoroethylene sheet.
Step 2, preparing a silk fibroin gradient gel/carbon nano tube double-layer structure: PDMS mold (4 cm. Times.0.5 cm. Times.0.1 cm) was placed on a carbon nanotube sheet, then the cross-linking reaction mixed solution of example 1 was injected, gelation was performed at room temperature, then the bilayer structure was peeled off from the polytetrafluoroethylene sheet to obtain a Carbon Nanotube (CNT)/silk fibroin uniform hydrogel bilayer structure system (designated SF-H-gel/CNT), an electric field was applied to the bilayer system with the carbon nanotube layer and ITO glass as anode and cathode to induce shape transition thereof, and a carbon nanotube/silk fibroin gradient hydrogel bilayer strip (designated SF-G-gel/CNT) was obtained.
The application of the silk fibroin gradient hydrogel as a bioelectrode is realized according to the following method:
a Carbon Nanotube (CNT)/silk fibroin uniform hydrogel bilayer (40 mm long by 1mm wide) was attached to the copper wire by conductive silver paste. In the sciatic nerve stimulation experiments, the New Zealand rabbit ear was anesthetized by intravenous injection of chloral hydrate (5 mg/kg). After shaving, a 10cm long skin incision was created, and the gluteus muscles near the buttocks were dissected to expose the sciatic nerve. A pair of hydrogel/carbon nanotube bilayer strip (SF-G-gel/CNT) electrodes deformed upon actuation of an electric field are wrapped around the exposed sciatic nerve, one of which is wrapped around the proximal sciatic nerve (near the spinal cord), connected to a signal generator, the other of which is wrapped around the distal sciatic nerve, and connected to an oscilloscope probe for receiving signals. The ground electrode is clamped to the skin adjacent the incision. The sciatic nerve was stimulated using 1Hz biphasic pulses generated by a signal generator (UPO 2104CS, unit-t, velleman), and an oscilloscope received and recorded the signals transmitted through the conductive electrode-sciatic nerve system. The foot angle change of new zealand rabbit 6 was then quantitatively analyzed by Image J software.
The photograph of the rabbit leg electrically stimulated with the bioelectrode prepared with silk fibroin gradient hydrogel is shown in fig. 7, and it can be seen that the undeformed electrode (SF-H-gel/CNT) has limited contact with the sciatic nerve and cannot cause leg movement, while the deformed electrode (SF-G-gel/CNT) tightly wraps the sciatic nerve. Under electrical stimulation (1-5 v,1 hz), a stable and periodic movement of the legs driven by the contraction of the muscles caused by the electrical stimulation of the sciatic nerve was observed. These results indicate that the deformed bioelectronics can more effectively deliver electrical signals to nerve tissue.